The Analysis of Phonology in First Language Acquisition Melayu Pattani in Children Three-Year-Old - Idda Astia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
The study aims at finding out how the children in Pattani, Thailand acquire their first language acquisition. The study is focused on the children of three-year-old due to the fact that they are able invited to communicate in two ways and already comprehend the time when their turn to talk and when other person’s turn to talk. Therefore, the researcher wants to research the utterances in process of first language acquisition in phonology. The study is conducted to address the language acquisition in Melayu Pattani due to the fact that it does not identify in Melayu Malaysia. In addition, the study uses a descriptive qualitative method for analyzing and describing the production of children's utterances. The data were taken by recording and interviewing the children. Finally, it is inferred that children absolutely do the simplification, such as substitution, omission, and assimilation to help them to produce the utterance when they make the conversation.